Psychometric properties of the SCREESCO questionnaire used in a colorectal cancer screening programme—A Rasch analysis. Issue 2 (22nd November 2019) - Jervaeus, Anna; Fritzell, Kaisa; Hultcrantz, Rolf; Wengström, Yvonne; Kottorp, Anders
Abstract: Introduction: Colorectal cancer (CRC) is one of the most common cancer diagnoses among both sexes. Sweden has not yet implemented any CRC screening programme, but a study, Screening of Swedish Colons (SCREESCO), is ongoing. The movement within the health care sector towards a more participatory perspective has led to the increased importance of shared decision making (SDM), and this is suggestively applied when deciding upon screening participation. There is no Swedish questionnaire for assessing the level of SDM in relation to CRC screening. Therefore, the CRC screening module of the National Survey of Medical Decisions was translated and culturally adapted into a Swedish context: the SCREESCO questionnaire. Aim: The SCREESCO questionnaire requires further evaluation, and therefore, the aim, by using the Rasch approach, was to evaluate the psychometric properties of the SCREESCO questionnaire. Methods: A Rasch partial credit model was chosen to investigate the psychometric properties. The sample consisted of individuals invited to the SCREESCO programme, who have answered the SCREESCO questionnaire. Results: Rating scale structures indicated stability for the response structure used. Satisfactory evidence for validity of internal structure was also shown for the whole questionnaire and two of three concepts/subscales, after deletion of a few items. Validity in response processes indicated acceptable, or close to acceptable, findings, while the results for unidimensionality and differential item functioning (DIF) were somewhat mixed. Separation index revealed less satisfactory results, both for the whole questionnaire and the concepts/subscales. Conclusion: This Rasch analysis of the SCREESCO questionnaire revealed that the questionnaire in its current form has difficulties to assess the level of SDM in relation to CRC screening. The achieved results will guide further evaluation and development with the long‐term goal of having a Swedish questionnaire, to be used in the health care sector, assessing the level of SDM in relation to CRC screening.